Hypothermic machine perfusion of a donor kidney using an experimental dextran-40-based preservation solution and orthotopic transplantation (experimental study) - V. G. Shestakova; V. K. Bogdanov; R. D. Pavlov; V. M. Terekhov; A. S. Timanovsky; A. A. Zharikov; A. N. Shibaev; N. V. Grudinin (Вестник трансплантологии и искусственных органов, 2024)
Objective: to evaluate the efficacy of hypothermic machine perfusion (HMP) of a donor kidney obtained from a non-heartbeating (NHB) donor, using an experimental dextran-40-based preservation solution, in subsequent orthotopic transplantation in a rabbit model.Materials and methods. Twenty grey giant rabbits weighing 2,500–3,100 g, divided into donors (n = 10) and recipients (n = 10), were used in the study. After obtaining kidney from an NHB donor, ex vivo HMP of the left donor kidney using a dextran-40-based preservation solution was performed and peripheral vascular resistance (PVR) parameters were measured. This was followed by bilateral nephrectomy and orthotopic transplantation. The follow-up period was 12 days. Creatinine levels, urea levels, and glomerular filtration rate (GFR) were measured during follow-up.Results. During ex vivo HMP of donor kidneys from NHBs, PVR dropped progressively from 1.90 ± 0.27 mmHg/mL/min to 0.72 ± 0.09 mmHg/mL/min at p < 0.001. In the early post-transplant period (during the first 2 days after implantation), creatinine and urea levels were moderately elevated compared to normal. Creatinine and urea levels were 91.07 ± 11.49 μmol/L at p < 0.011 and 9.09 ± 1.06 mmol/L at p < 0.009 on day 2, respectively, but by day 12, they reverted to physiologic values, which were 77.17 ± 10.19 μmol/L at p < 0.019 and 4.88 ± 0.54 mmol/L at p < 0.022, respectively. These findings were correlated with GFR values, which ranged from 26.29 to 26.74 mL/min/1.72 m2 in mean values over the course of a 12-day follow-up period.Conclusion. Ex vivo HMP using dextran-40-based preservation solution has a positive effect on the kidney at 30 minutes of warm ischemia following asystole and achieves satisfactory graft function over 12 days of follow-up.